Evaluations of deep learning methods for detection of gap in concrete structures - Yang, Zhen (Nanyang Technological University, 2021)
This dissertation applies 3 networks(FRCNN,Yolov3,Yolov4) to solve gap detection on a very small data set and make brief evaluations about their structures and performances.